What is our value and who values us? - Goetsch, Lori A. (My University, 2009)
As an academic librarian for nearly 30 years, I have experienced many of the challenges that we face at our home institutions. Today, the current economic climate has created a particularly daunting challenge and a sense of vulnerability. Staff are furloughed, service hours are cut, positions go unfilled, and the acquisition of materials cannot keep up with user needs.
Citation: Goetsch, Lori A. “What is our value and who values us?: The 2009–10 ACRL President’s focus,” College and Research Libraries News October 2009 70:502-503.
Keywords: Information Science; Association of College & Research Libraries